2017
DOI: 10.1021/acs.chemmater.7b03195
|View full text |Cite
|
Sign up to set email alerts
|

Single Magnetic Impurities in Colloidal Quantum Dots and Magic-Size Clusters

Abstract: Impurity doping can be used to dramatically alter the physical properties of semiconductor nanostructures and endow them with promising new technological potential. This review summarizes recent progress toward the development of colloidal semiconductor quantum dots (QDs) doped with individual magnetic impurity ions. Such singly doped quantum dots (SDQDs), as well as related magic-sized nanoclusters, represent an exciting class of materials for cultivating unique physical effects arising from magnetic exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 135 publications
1
37
0
Order By: Relevance
“…[67,[87][88][89] Incorporation of open-shell magnetic impurities with nonmagnetic semiconductors leads to coupling of the localized unpaired spins with the relaxed photogenerated electron-hole pair (exciton), which is termed as sp-d exchange interactions (s-d and p-d interaction indicates coupling of dopants with electrons and holes, respectively). [90] The excitonic Zeeman splitting of DMSs considering the sp-d exchange induced contribution is quantitatively expressed by Equation (6) [91] Zeeman…”
Section: Characterization Of Sp-d Exchange Interactions In Diluted Mamentioning
confidence: 99%
See 3 more Smart Citations
“…[67,[87][88][89] Incorporation of open-shell magnetic impurities with nonmagnetic semiconductors leads to coupling of the localized unpaired spins with the relaxed photogenerated electron-hole pair (exciton), which is termed as sp-d exchange interactions (s-d and p-d interaction indicates coupling of dopants with electrons and holes, respectively). [90] The excitonic Zeeman splitting of DMSs considering the sp-d exchange induced contribution is quantitatively expressed by Equation (6) [91] Zeeman…”
Section: Characterization Of Sp-d Exchange Interactions In Diluted Mamentioning
confidence: 99%
“…An exceptionally high excitonic g-factor of − 907 was achieved with x = 0.19 at 1.8 K. On the other hand, fabricating semiconductor nanocrystals with single dopant will benefit coherent optical spin manipulations for solotronic information processing technologies. [91,97,98] Fainblat et al reported successful doping of colloidal CdSe QDs with a very small number of dopants down to single Mn 2+ ion. [99] The singly doped QDs showed enhanced excitonic Zeeman splitting that was dominated by sp-d exchange interactions.…”
Section: Characterization Of Sp-d Exchange Interactions In Diluted Mamentioning
confidence: 99%
See 2 more Smart Citations
“…14 Recently developed 'solotronic' nanocrystals, in which a single impurity or defect is present in a semiconductor nanocrystal, exhibit remarkable properties. [15][16][17] Optical or electrical stimulus of quantum dots with single atom manganese impurity led to specic changes in the manganese spin state, 18,19 and gave rise to well-resolved splitting of the photoluminescence due to the spin projections of the S ¼ 5/2 Mn 2+ ion. 20 Despite signicant advances in the synthesis of doped nanocrystals, the ability to selectively locate impurities at specic sites (substitutional vs. interstitial), control the concentration and spatial density of the impurity in the host, and control the charge compensation mechanism remain as open challenges in the preparation of doped nanocrystals.…”
Section: Introductionmentioning
confidence: 99%